2015
DOI: 10.1016/j.cellimm.2015.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Microparticulate β-glucan vaccine conjugates phagocytized by dendritic cells activate both naïve CD4 and CD8 T cells in vitro

Abstract: Microparticulate β-glucan (MG) conjugated to vaccine antigen has been shown to serve as an effective adjuvant in vivo. To further study antigen presentation by MG:vaccine conjugates, bone marrow-derived dendritic cells (BMDC) were treated with MG conjugated to ovalbumin (OVA), then interacted with splenocytes from DO11.10 transgenic mice expressing an OVA peptide-specific T cell receptor. BMDC treated with MG:OVA induced significantly higher numbers of activated (CD25+CD69+) OVA-specific CD4+ T cells than BMDC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 37 publications
0
13
0
1
Order By: Relevance
“…The BSA-GP conjugates were phagocytized by macrophages and both intradermal and oral administration of BSA-GP vaccine induced immune responses against BSA. OVA-GP conjugates were synthesized similarly, which induced strong BMDC, CD4 + and CD8 + T cells activation in vitro (Berner et al, 2015). The Hong group prepared OVA loaded GPs in organic phase, which reduced GP aggregation compared to aqueous phase conjugation, and provided more homogenous OVA-GPs (Yang et al, 2017).…”
Section: β-Glucansmentioning
confidence: 99%
“…The BSA-GP conjugates were phagocytized by macrophages and both intradermal and oral administration of BSA-GP vaccine induced immune responses against BSA. OVA-GP conjugates were synthesized similarly, which induced strong BMDC, CD4 + and CD8 + T cells activation in vitro (Berner et al, 2015). The Hong group prepared OVA loaded GPs in organic phase, which reduced GP aggregation compared to aqueous phase conjugation, and provided more homogenous OVA-GPs (Yang et al, 2017).…”
Section: β-Glucansmentioning
confidence: 99%
“…The adjuvant effect of Dectin-1 ligation in T-cell immunity is undisputed, and it has been proven that Curdlan can polarize T-cell responses ( 99 , 100 ). In line with these data, it has been shown that anti-Dectin-1 stimulation and the application of microparticulate β-glucan conjugates can potentiate an ovalbumin-specific CD4 + T-cell response ( 101 , 102 ). It was also described that Curdlan treatment can switch a Th2 to a Th1 response in tumor immunology ( 103 ).…”
Section: Resultsmentioning
confidence: 58%
“…The carbohydrate surface of GPs can be covalently modified using sodium periodate (NaIO 4 ) oxidation–borohydride reduction, carbodiimide‐cross‐linking or 1‐cyano‐4‐dimethylaminopyridinium tetrafluoroborate‐mediated conjugation of antigens to the GP shell. GPs cross‐linked to ovalbumin (OVA) using the carbodiimide method activated bone marrow‐derived DCs to prime OVA‐specific CD4 + and CD8 + T cells in vitro . OVA can be cross‐linked to periodate‐oxidized GPs with 20% coupling efficiency (calculated on a weight basis).…”
Section: Gps Covalently Cross‐linked To Antigensmentioning
confidence: 99%
“…GP‐OVA were found in the DCs (CD11c + MHC‐II + ) in lymph nodes 12 and 36 h post‐subcutaneous injection . The tumour protective effects were associated with an increase in total immunoglobulin (Ig)G titre, enhanced MHC‐II and co‐stimulatory molecule (CD80, CD86) expression and heightened CTL responses . In infection models, administration of GPs conjugated to bovine serum albumin (BSA) at a lower dose (0·6 mg) protected mice challenged with the fungal pathogens Aspergillus fumigatus and Coccidioides posadasii marginally more effectively than GP‐alone immunization .…”
Section: Gps Covalently Cross‐linked To Antigensmentioning
confidence: 99%